Q-master for jam session / Khairuddin Mohd Ardzi and Mohd Fazli Ahmad - Mohd Ardzi, Khairuddin; Ahmad, Mohd Fazli (2004)
In a jam session, for example in a game or a quiz, there must be a series of contestant and the most important is the Quizmaster. This device, “Q master” can be designed so that it is easier for the quizmaster to gain control of the game. This device will help the quizmaster to determine which contestant push the button first and give the right contestant to answer the question. After the quizmaster read the question, he will push a button to give the contestants signal to push the button. An LED will light up for this purpose. The display will show which contestant should have the first tum to answer the question. This device is very useful for the quizmaster and it will help the game to run smoothly.